Żywe łańcuchy dostaw jako przedmiot zarządzania projektem - Kisperska-Moroń, Danuta (Living Supply Chains as a Subject of Project Management, 2008)
Logistics and supply chain management has become very dynamic and constantly changing due to its service role for the majority of economy sectors. Due to the temporary character and the change of adapted solutions, according to market evolution, the way of operation of present supply chains could be considered as parmanent change management. The necessity to adapt to the environment seems to be the direct reason for the reconstruction of logistics processes. Hence one can consider adaptive management, being based on agile revolution, use of values and rules of agile management and precise practices that create those values. Supply chains evolve much like during biological evolution, though their evolution is significantly faster. The scheme of such evolution is quite similar: the mutation and recombination of elements, the survival of the strongest organisms and the copying of those that survive. Thus one can consider the subsequent organizational metaphors of supply chains as "living" supply chains. It also requires the change of the concept of traditional planning stages and of project structure where minimum of principles is supported with cooperation and interaction within the framework of project community.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 51-61